How Do Muslim Communities Create Peace in Schools? Urban School Climate (USC) Model as a Prevention of Bullying - Fauziah, R. Siti Pupu; Roestamy, Martin; Yazdi Martin, Abraham; Moyana, Nova; Suherman, Irman; Warizal, Warizal (Jurnal Pendidikan Islam, 2025)
This study examines the behavioral dynamics and social interactions of Muslim school communities by situating them within the ethical framework of the Qur’an and the teachings of the Prophet Muhammad. Although numerous studies have highlighted the importance of school climate and social relations in shaping educational outcomes, limited attention has been given to how Islamic values concretely inform these processes within Muslim educational contexts. To address this gap, a qualitative case study approach was employed, focusing on patterns of behavior and interaction in Muslim school communities. Data were collected through observation, interviews, and document analysis, and subsequently analyzed using a thematic analysis approach. The findings reveal that the Qur’an and Hadith serve not only as spiritual references but also as practical guidelines for cultivating a safe and supportive learning environment, strengthening teacher–student and peer relationships, and reinforcing the influence of family in students’ character formation. These interactions collectively foster a school climate characterized by harmony, inclusivity, and mutual respect. By linking Islamic normative principles with contemporary educational practices, this study underscores the role of religion as a transformative resource in promoting holistic education. The results offer valuable insights for educators, policymakers, and researchers seeking to improve the quality of Islamic education while contributing to broader discussions on values-based education in global contexts.